Nonfamilial Juvenile Polyposis Syndrome with Exon 5 Novel Mutation in SMAD 4 Gene - Amna Ahmed; Badr Alsaleem (Case Reports in Pediatrics)
Juvenile polyposis syndrome (JPS) is a rare autosomal dominant hereditary disorder, characterized by multiple juvenile polyps in the gastrointestinal tract and an increased risk of colorectal cancer. JPS is most frequently caused by mutations in the SMAD4 or BMPR1A genes. Herein, we report a child with juvenile polyposis syndrome (JPS) with a novel mutation in the SMAD4 gene. An 8-year-old boy presented with recurrent rectal bleeding and was found to have multiple polyps in the entire colon. The histology of the resected polyps was consistent with juvenile polyps. Subsequent genetic screening revealed a novel mutation in SMAD4, exon 5 (p.Ser144Stop). To the best of our knowledge, this mutation has not been reported before. Offering genotypic diagnosis for patients with JPS is an important step for strategic plan of management.